ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9414642
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Task Estimation of Age and Cognitive Decline from Speech

Abstract: Speech is a common physiological signal that can be affected by both ageing and cognitive decline. Often the effect can be confounding, as would be the case for people at, e.g., very early stages of cognitive decline due to dementia. Despite this, the automatic predictions of age and cognitive decline based on cues found in the speech signal are generally treated as two separate tasks. In this paper, multi-task learning is applied for the joint estimation of age and the Mini-Mental Status Evaluation criteria (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Specifically, after proposing three deep learning architectures based on CNNs and RNNs, the authors applied visualization techniques and showed which linguistic characteristics are indicative of dementia, i.e., short answers, repeated requests for clarification, and interjections at the start of each utterance. Authors in [25] proposed a multi-task learning framework (Sinc-CLA), so as to predict age and MMSE scores (both considered as regression tasks) and used only speech as input for their proposed network. Concurrently, they introduced shallow networks with input i-vectors and x-vectors both in single and multi-task learning frameworks.…”
Section: B Deep Learningmentioning
confidence: 99%
“…Specifically, after proposing three deep learning architectures based on CNNs and RNNs, the authors applied visualization techniques and showed which linguistic characteristics are indicative of dementia, i.e., short answers, repeated requests for clarification, and interjections at the start of each utterance. Authors in [25] proposed a multi-task learning framework (Sinc-CLA), so as to predict age and MMSE scores (both considered as regression tasks) and used only speech as input for their proposed network. Concurrently, they introduced shallow networks with input i-vectors and x-vectors both in single and multi-task learning frameworks.…”
Section: B Deep Learningmentioning
confidence: 99%
“…Language functioning can provide valuable insights into cognition and behavior, serving as a window into an individual's cognitive functioning [7][8][9][10][11][12]. Speech and language offer an opportunity to use ecologically valid methods to assess key symptoms related to cognitive function, a unique advantage in the assessment and monitoring of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…The growing prevalence of cognitive impairments, like dementia, coupled with the current limitations in diagnostic approaches, underscores the urgent need for a robust Remote Patient Monitoring (RPM) system. Such a system would be instrumental in the early identification of cognitive decline, enabling ongoing monitoring of its progression [11]. In this context, the development of a wearable device, functioning as an RPM tool, could significantly bridge this gap.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there is a line of work that utilize multi-task learning to estimate age and another speaker attribute, such as gender [13], and emotion [14]. [15] applied a multi-task learning for the joint estimation of age and the Mini-Mental Status Evaluation criteria, showing improved performance on input features including i-vector and x-vector.…”
Section: Introductionmentioning
confidence: 99%